If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -4 = 9x + 16 Reorder the terms: -4 + 13x = 9x + 16 Reorder the terms: -4 + 13x = 16 + 9x Solving -4 + 13x = 16 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -4 + 13x + -9x = 16 + 9x + -9x Combine like terms: 13x + -9x = 4x -4 + 4x = 16 + 9x + -9x Combine like terms: 9x + -9x = 0 -4 + 4x = 16 + 0 -4 + 4x = 16 Add '4' to each side of the equation. -4 + 4 + 4x = 16 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 16 + 4 4x = 16 + 4 Combine like terms: 16 + 4 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| 3xy=15 | | X^3+6x=29 | | 2+w+w+7h+3w= | | -89=3(1+5n)-2 | | 2p-7(6-p)=-96 | | (u+2)(u-1)=0 | | 6(4x+y)-7(3x+5y)= | | m-2y=1 | | x*x-2x+45=0 | | 5-3x=-2 | | f(x)=x^6-16x^4-81x^2+1296 | | 8x-9-6x=6 | | (4w-3)(6-w)=0 | | 1.2=-1.2b | | 11x-5[4(x+1)]=x | | 102=-4(3x-6)-6 | | 2x-10=-5y | | x=53 | | 5+(4x-6)= | | 3x*x+6x-40=0 | | (v+3)(v+5)=0 | | -3x+15(x-2)=x | | 5(-6x-3)+5x=-2 | | 9(3x+5)=x | | 17.1timesn=200 | | -7z+1=-5z-9 | | x+2yi=3-6i | | 10(3+9m)+8m= | | 4-2=5 | | -90+4(5+11)=x | | 10+d=-34-5d | | 9abs(9-8x)=2x+3 |